The Effect of Lactation Education on Increasing Knowledge of Breastfeeding Mothers at Manembo-Nembo Hospital, Bitung City - Philia Phoebe Pangandaheng; Reny Retnaningsih (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Breastfeeding success is greatly influenced by the mother's level of knowledge, especially during the early postpartum period, which is a crucial adaptation phase in the lactation process. Lactation education is a strategic intervention to improve mothers' understanding of the benefits of breast milk, proper breastfeeding techniques, and management of lactation problems. This study aims to analyze the effect of lactation education on improving mothers' knowledge of breastfeeding at Manembo-Nembo Hospital, Bitung City. This study used a quasi-experimental design with a one-group pretest–posttest approach. The study sample consisted of 30 mothers selected using a purposive sampling technique. Knowledge levels were measured before and after lactation education using a structured questionnaire. The lactation education intervention was delivered through interactive lectures, discussions, and demonstrations of breastfeeding techniques. Data were analyzed univariately and bivariately using the Wilcoxon Signed Rank Test with a significance level of p < 0.05. The results showed an increase in mothers' knowledge after lactation education. The distribution of knowledge levels shifted to the better category, and the Wilcoxon test results showed a significant difference between knowledge scores before and after the intervention (p < 0.05). The conclusion of this study indicates that lactation education significantly improved maternal breastfeeding knowledge. Lactation education can be used as an effective intervention in postpartum care in hospitals to support successful breastfeeding and improve the quality of midwifery care.